Block length and topology affect self-assembly and gelation of poly(l-lysine)-block-poly(S-benzyl-l-cysteine) block copolypeptides. (16th July 2021) - Tang, Chen-Chi; Zhang, Song-Hao; My Phan, Thi Ha; Tseng, Yu-Chao; Jan, Jeng-Shiung
Abstract: We report the self-assembly and hydrogelation of linear and star-shaped poly(l -lysine)- block -poly(S-benzyl-l -cysteine) (PLL- b -PBLC) block copolypeptides with degrees of polymerization (DPs) between 15 and 70, driven by the amphiphilic balance between PLL and PBLC segments as well as both aromatic and hydrogen bonding interactions between PBCL segments. The hydrogelation ability, molecular assembly, and mechanical strength of PLL- b -PBLC could be tuned by manipulating the non-covalent interactions via varying polypeptide chain length and arm number. The confinement of PLL chains due to the packing of hydrophobic, sheet-like PBLC segment led to the percentage of β-sheet/turn conformation much higher than the mole fraction of PBLC segment, faciliating polypeptide self-assembly and hydrogelation. Due to the differences in the degree of freedom for linear and star-shaped polypeptides to self-assembly, the linear PLL- b -PBLC would undergo morphological transformation of the nano-assemblies from 2D bilayers to 3D spherical aggregates upon hydrogelation, but not for the star-shaped counterparts. This study clearly illustrated that the sheet-like PBCL segment is an excellent hydrogelator to trigger hydrogelation of these block copolypeptides. Graphical abstract: The self-assembly and hydrogelation of linear and star-shaped PLL- b -PBLC block copolypeptides were driven by the amphiphilic balance between PLL and PBLC segments as well as the hydrogen bonding and aromatic interactions between PBLC segments. Image 1 Highlights: The first report on synthesizing star-shaped block copolypeptides using readily available alcohols as the initiators. The hydrogelation was driven by the amphiphilic balance and the hydrogen bonding and aromatic interactions between PBCL segment. Linear PLL- b -PBLC would undergo sol-to-gel transition with morphological transformation of the nano-assemblies. Self-assembly of linear ones transformed from 2D bilayers to 3D spherical aggregates upon hydrogelation. Star-shaped ones exhibited little change in morphology upon hydogelation due to their relatively lower degree of freedom.